1994
DOI: 10.1002/j.1556-6978.1994.tb00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Structured Group Supervision (SGS): A Pilot Study

Abstract: The article reports the pilot study results of a Structured Group Supervision (SGS) model. The structured model of group supervision seemed superior in comparison with “control” group supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 34 publications
2
48
0
Order By: Relevance
“…A second technique that we have incorporated, also borrowed from the group supervision literature, involves a structured process during which the presenting supervisee presents a clear plea for help (Wilbur, Roberts-Wilbur, Hart, Morris, & Betz, 1994), stated as, "I need your help with . .…”
Section: In-session Strategiesmentioning
confidence: 99%
“…A second technique that we have incorporated, also borrowed from the group supervision literature, involves a structured process during which the presenting supervisee presents a clear plea for help (Wilbur, Roberts-Wilbur, Hart, Morris, & Betz, 1994), stated as, "I need your help with . .…”
Section: In-session Strategiesmentioning
confidence: 99%
“…Because of the lack of basic research in this area, Prieto (1996), Wilbur et al (1994), and Werstlein and Borders (1997) contended that initial exploratory group supervision research is necessary. Prieto (1996), Holloway and Johnston (19851, and Borders (1991) also argued that group supervision research should be exploratory and discovery oriented.…”
mentioning
confidence: 98%
“…Based on previous models and contentions regarding the efficacy of peer group supervision, Borders (1991) and Wilbur, Roberts-Wilbur, Hart, Morris, and Betz (1994) developed specific procedures regarding how to structure peer supervision groups. Most recently, research related to structured peer group supervision includes Starling's (1995) qualitative study of practicum supervisees.…”
mentioning
confidence: 99%
“…71 to .77. Wilbur et al (1994) suggested that these items fell into the skills development category of the original design of the CSPD-RF (Wilbur et al, 1994). (Such items are similar to the microskills suggested by Smaby et al, 1999.…”
Section: Factor Structurementioning
confidence: 95%
“…According to the original authors of the CSPD-RF, 10 items measure personal development, and 10 measure skills development (Wilbur et al, 1994). Originally, the CSPD-RF used a 7-point Likerttype scale.…”
Section: Instrumentmentioning
confidence: 99%